A numerical study of the effect of ply-layup on the strength and stiffness of a composite T-joint under three point bending. Issue 19 (18th October 2017) - Azam, Ammar; Mubashar, Aamir; Ashcroft, Ian Anthony; Uddin, Emad; Jaffery, Syed Husain Imran
Abstract: This paper discusses the effects of various ply-layup orientations on the bending stiffness of a composite T-joint by determining the in-plane and out-of-plane stress fields developed under three-point bending conditions. The failure load and crack development in the T-joints with selected ply-layups are also considered. A three dimensional finite element model of the composite T-joint was developed and validated by comparison with experimental results. Five selected ply-layups were applied to the validated composite T-joint model and in-plane as well as out-of-plane stress fields investigated. It was found that bending stiffness was primarily influenced by plies that came under tension during the application of the force. Symmetric layups with ply angles that cancel the tensile stiffening effects reduce the bending stiffness. No appreciable out of plane coupling effects were observed and thus the overall magnitudes of the out of plane shear forces were not significant when compared with in-plane stresses. Damage initiated at the sites of stress concentration at the ends of the adhesive layer and cracks propagated towards the middle of the T-joint.